Body and biology - Roberto Cipriani (Academicus, 2020)
The social community is neither a mosaic nor a sum of different identities but something akin to a new, compound being, characterised by its own genome: the mfDNA. It involves, in particular, a kind of colonisation, the outcome of events, contingencies, probabilistic dynamics, interrelationships between the individual (or society) and the environment. Furthermore, community does not imply a mere list of species but a milieu that exists to serve their relative, not simply single and bi-univocal representations and interrelationships, acting within a complex multifactorial network characterized by a preliminary mathematical-model approach. Therefore, it is possible to introduce a new perspective, driven by the mfDNA approach and biology, and suggest a wider context capable of improving our understanding of the role of individuals within societies. We propose a new tool, the “social mfDNA model”, as an interior indicator of the properties, composition and dynamics of human society.